Value Chain-Based Quantification of Embodied Flows of Global Urea Fertilizer: An Environment-Economy Nexus Analysis - Gill, Muhammad Yasin; Chen, Jinpu; Qadeer, Shazia; Fan, Ying; Li, Xiao; Ali, Tariq; Liu, Yihong; Xia, Xiaohua; Li, Zhi (Journal of Environmental Accounting and Management, 2026)
Given the projected rise in food requirements for the growing world population, urea fertilizer remains essential for sustaining large-scale food production, despite its significant environmental impacts, including greenhouse gas emissions and water contamination. We develop an updated value chain-based Input-Output Analysis (IOA) and use the FAO and Eora data to quantify the local utilization and global trade of urea fertilizer within the supply chain, assessing fractions for environmental impacts and market trends to inform agricultural practices. The IOA framework explores global urea trade, embodied intensities, value-added, production, and supply chain dynamics, identifying sustainable practices and policy opportunities. Our findings indicate significant discrepancies in embodied intensities and the consumption of chemical fractions across world economies, which lead to environmental issues such as soil depletion and greenhouse gas emissions. Total embodied urea fertilizer consumption is estimated at 142.38 million tons per year, substantially exceeding actual usage, indicating inefficiencies and potential areas for implementing sustainable practices. Key agricultural countries, including India, exhibit trade dependencies that render their agricultural sectors susceptible to geopolitical risks. This work supports future efforts to mitigate environmental impacts and improve sustainability in agriculture.